Creativity among musically trained and untrained girl students - Alizadeh, Shahla; Hassan, Siti Aishah; Tafti, Mahnaz Akhavan (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The purpose of this study is to compare the creativity of musically trained and untrained third grade high school and first grade guidance school girl students. The sample of this study consist of 93 students from first grade guidance and third grade students in the academic year 1383-84 in Tehran. The research method is causal comparative and the research tool is Torrance Test of creativity (1974) with a reliability 0.63. The results show creativity scores of musically trained student in Torrance test of creativity and subtest (fluency, flexibility, initiative and originality) are higher than the untrained students. The creativity scores of trained students who learned music before age 10 are also higher than others who started after this age. This investigation has shown that music training plays a great role on creativity of students suggesting that music teaching should be started in schools along with other lessons preferably before age 10. In conclusion, it is suggested that the parents need to encourage the children to be involved in music during their childhood years. By participating in music class, both the parents and children may spend quality time together.